"If You Could Wave a Magic Wand": Treatment Barriers in the Rural Midwest. (December 2021) - Clark, Angela; Lanzillotta-Rangeley, Jennifer; Stem, Jack
Introduction: The multigenerational health considerations and negative economic impacts related to the opioid epidemic are many. Increasing numbers of opioid-related fatalities are bolstered by barriers related to access to evidence-based treatment. Ohio is ranked second in the country for number of opioid-related deaths, and for many their treatment needs remain unmet due to impaired access to effective treatment, in rural, medically underserved areas of the state. Purpose: The goal of this study was to assess opioid use disorder treatment barriers in order to increase access to evidence-based treatment, wrap around services, and harm reduction efforts to support the reintegration of persons with substance use disorder back into society and subsequently reduce opioid fatalities in a rural, medically underserved region of Ohio. Methods: As part of a larger mixed-methods study design where a community health survey was randomly distributed to residents in a rural county in Ohio, this study used qualitative methods to triangulate findings. To supplement the data received from the surveys, 20persons with a diagnosed opioid use disorder (OUD) took part in focus group sessions guided by trained researchers. The sessions were transcribed, and the data was analyzed using Braun and Clarke's thematic analysis method. Results: Three major themes emerged from the data: epigenetics and exposure, management of disease including re-integration into society, and disease process. The participant data created insight regarding the need to recognize OUD as a chronic condition that must be addressed with integrated components of medical, behavioral, and mental health morbidities throughout the lifespan and across generations. Conclusions: Findings from this study support the need for targeted interventions for integrated care and improved wrap around services such as transportation, sober living, and employment.